Relationship of Type 2 Diabetes Mellitus Duration with The Occurrence of Erectile Dysfunction at Puskesmas Denpasar Barat I - Alexander Petra Sihite; I Gusti Ngurah Pramesemara; I Wayan Surudarma (Universitas Airlangga, 2021)
Background: Type 2 diabetes mellitus is a metabolic disease that characterized by high blood sugar levels. This condition is often not noticed immediately and usually patient starting to realize it when complications have been occurred. A long-term complication of type 2 DM that occurred in men is erectile dysfunction (ED). ED is a condition when a person is unable to achieve or maintain an erection for sexual intercourse. One factor that influence the occurrence of ED and its severity in type 2 DM patients is the duration of the disease. Objective: The aim of this study was to determine the relationship of type 2 DM duration and the occurrence of ED. Methods: This study is an observational analytic cross-sectional study conducted at the Puskesmas (Public Health Center) Denpasar Barat I. The research data was obtained through medical record data and fill the International Index of Erectile Function (IIEF-5) questionnaire on 36 type 2 DM patients aged around 40-60 years. The statistical analysis used was Fisher's exact test. Results: The results showed that of the 36 samples, 19 (52.8%) samples had type 2 DM <24 months and 17 (47.2%) samples had type 2 DM >24 months. It was found that 5 (13.9%) samples did not experience ED while the rest experienced ED with different severity. There was a significant relationship between the type 2 DM duration and the occurrence of erectile dysfunction at Puskesmas Denpasar Barat I (p = 0.022). Conclusion: Study has found that type 2 DM patients with the longer duration (>24 months) have a higher occurrence of ED and tended to be more severe compared to those with shorter duration (<24 months). Further studies should be performed with higher number of patients and more controlled risk factor so it will be more accurate in determining the relationship between the duration of type 2 DM and ED.